The Multifaceted Therapeutic Potential of Saffron: An Overview Based on Research and Patents - Yahya Ramadan Elfardi; Reda El Boukhari; Ahmed Fatimi; Latifa Bouissane (MDPI AG, 2024)
Plants and plant extracts have long been acknowledged as valuable resources for the development of therapeutic formulations for various diseases. Among them, numerous plants and plant-derived products have demonstrated cytotoxic and/or anti-tumor properties. Saffron, particularly due to its major compounds, namely crocin, crocetin, and safranal, stands out as a promising candidate in this regard. Our research undertakes a literature review, reaffirming the antioxidant, anti-inflammatory, and, notably, anti-tumor properties of saffron and its major constituents. Additionally, this study examines relevant patent documents, highlighting innovative applications for saffron and its major compounds in cancer therapy. The review discusses the progress in purifying the compounds extracted from saffron and assesses their impact on cytotoxic trial outcomes, the potential synergies between certain saffron compounds and established cytotoxic molecules, and the limitations of the patents examined, particularly concerning reported clinical evidence. Researchers who focus on advances in oncology will know from our findings the evolution of the patent landscape regarding cytotoxic and/or anti-tumor therapeutic applications using saffron or its main compounds. Moreover, investigators can draw inspiration from patents leveraging traditional knowledge, particularly from Chinese medicine, to clarify specific active molecules and their mechanisms of action and can expedite the translation of these findings into clinically relevant interventions, potentially enhancing cancer therapy outcomes.